The evolution of perfusion education in America. - Toomasian JM; Searles B; Kurusz M (Perfusion, 2003)
Clinical cardiopulmonary perfusion has evolved significantly during its 50 years. The science, technology and educational processes related to cardiopulmonary bypass have undergone continual change and metamorphosis. Perfusionists were initially trained on the job or in the laboratory, but with the advent of myocardial revascularization and the explosion in cardiac surgery, the need for formal educational training programs became apparent. The American Society of Extracorporeal Technology began the arduous processes of credentialing and developing certification guidelines that have continued under the American Board of Cardiovascular Perfusion. Licensure has also been adopted in many states during the past 10 years where nearly 50% of all perfusionists are covered by some legislative act. One additonal challenge has been developing minimal standards in which perfusionists practice. The initial standards included the use of a checklist and have evolved to monitoring and recording the significant events and parameters of each clinical procedure. The education of perfusionists will continue to be a challenge related primarily to reduced fiscal resources, the applicant pool and the ever-changing demands for extracorporeal circulation services. According to demographic and census information, it is expected the overall number of cardiovascular interventions will increase dramatically towards the latter end of the current decade in the US. The question arises as to what role perfusionists will play, as treatment strategies continue to change. If the number of education programs and new graduates continue to decline, the total number of perfusionists will decline, especially as many senior perfusionists leave the field or retire. It may be difficult to predict the total number of cardiovascular interventions that will be required in the next several years. However, if the total number of cardiovascular interventions that require perfusion services increase as a function of the aging population and if the overall incidence of cardiovascular treatment does not change, it will be imperative that perfusion education ramp up and train more perfusionists to meet the supply and demand or a shortage of skilled personnel may develop.